Chaplin's Essanay comedies, part 3 - Chaplin, Charlie 1889-1977. (Fremont, Calif. Essanay Film Mfg., Co., 1915)
Charlie gets shanghaied in a ship whose owner plans to destroy it to claim insurance money. Charlie goes to the theater, tries several seats and finally gets into a fight with the conductor. Charlie as Darn Hosiery is seduced by gypsy girl Carmen, leading to his disgrace and downfall. Charlie gets into several troubles with the police after he is freed from prison. In Triple trouble, Charlie plays a janitor who gets caught in the middle of a plot to steal explosives.
Shanghaied (27 min.) -- A night in the show (24 min.) -- Burlesque on 'Carmen' (1 hr., 12 min.) -- Police (25 min.) -- Triple trouble (23 min.)
VCD.
Produced for video by David Shepard.
Keywords: Tramps -- Drama; Comedy films; Silent films; Short films